Pengaruh Upah Minimum, Tingkat Pendidikan dan Literasi Digital Terhadap Pengangguran - Syamiya, Estu Niana; Latuconsina, Hudaya; murdy, khairi; Rahmah, Alfia (Universitas Negeri Padang, 2023)
Research has problems such as the ever-increasing number of unemployed, as well as the inflation rate. Therefore, the aim of this research is to (1) find out the picture of economic growth, inflation and unemployment in the city of Tangerang. (2) determine of the effect of the minimum wage on unemployment .3) determine effect of education level on unemployment. (4) knowing the effect of understanding digital literacy on unemployment. Survey method with quantitative descriptive analysis. Sampling used simple random sampling technique with a Guttman, Nominal, and Likert scale measuring instrument and an error rate of 5%. The sample in this study is the community in the Karang Tengah District, Tangerang City. The results is the minimum wage has a positive on unemployment, education level has a negative but significant effect on unemployment, and understanding of digital literacy has no and insignificant effect on unemployment. The novelty is namely using primary data such as a questionnaire besides using secondary data that comes from BPS